2011
DOI: 10.1007/s12070-011-0215-9
|View full text |Cite
|
Sign up to set email alerts
|

Giant Mastoid Emissary Vein: Source of Profuse Bleeding During Mastoid Surgery

Abstract: The emissary veins are residual connections between intra-cerebral veins and their extra-cranial drainage. Mastoid emissary vein is a rare but definite entity which if not diagnosed preoperatively could be a cause of severe hemorrhage at the time of surgery which may prove to be life threatening. These veins may vary in size from that of a mere thread to that of a wax match or 1/8th-3/8th of an inch. We report one such case of a giant mastoid emissary vein which was opened while operating on mastoid and caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“… 6 Preoperative knowledge of these veins could assist surgeons in preventing potential complications such as profuse bleeding, tinnitus, thrombosis, and infections. 13 14 15 Any potential surgery in the mastoid region requires a thorough evaluation of the relevant skeletal structures. A review of the English-language literature revealed a dearth of studies on this anatomical variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Preoperative knowledge of these veins could assist surgeons in preventing potential complications such as profuse bleeding, tinnitus, thrombosis, and infections. 13 14 15 Any potential surgery in the mastoid region requires a thorough evaluation of the relevant skeletal structures. A review of the English-language literature revealed a dearth of studies on this anatomical variant.…”
Section: Discussionmentioning
confidence: 99%
“…Emissary veins can measure anywhere between 1 mm and 4 mm. 13 14 If they are more than 3.5 mm in diameter, then they are considered prominent or enlarged mastoid emissary veins. 8 13 In our case, the maximum diameter of the vein was over 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, bleeding is trivial and can be easily controlled by plugging any openings with gauze or bone wax; however, in the cases of large EVs, it may be troublesome. 15 Moreover, late bleeding from EVs may also result in postoperative epidural hematoma formation. 4,16 Although the most appropriate material, including fibrin glue, should be inserted into a bleeding emissary foramen, care should be taken when using these materials; for example, bone wax applied to a bleeding emissary foramina has been known to enter the deeply placed venous sinuses and result in extensive thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is important for these veins to be assessed using preoperative imaging techniques, because they may represent a source of bleeding and air embolism during surgery. [8][9][10] However, many surgeons fail to pay these veins sufficient attention. 11 The number of radiological studies of the emissary veins is limited.…”
Section: Introductionmentioning
confidence: 99%